Medical Interpreter Challenges During Inperson Interpretation Session: A Systematic Review - Aisyah Jahidah Samsudin; Tg Ainul Farha Binti Tg Abdul Rahman; Hayati Binti Ismail (Allied Business Academies Publishing, 2024)
Indexed by Scopus